Kagome truss structure compression testing and three-point bending simulation - simulation in abaqus cae - Goh, Jia Cong (2017)
This Final Year Project (FYP) explores compression testing on kagome and Strut-Reinforced Kagome unit trusses to modelling and simulation of kagome truss structures. First, the models were created in SolidWorks, then 3D printed and physically tested. The truss structures are also modelled similarly and tested in Abaqus/CAE. Three-point bending is the selected testing procedure.